2013
DOI: 10.1159/000351257
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Benefit for Patients with Non-Small Cell Lung Cancer Enrolled in Phase I Trials

Abstract: Aim: To analyze the clinical features and outcomes of advanced non-small cell lung cancer (NSCLC) patients treated in phase I trials. Patients and Methods: The clinical characteristics, efficacy and toxicity data of 70 pretreated NSCLC patients enrolled in 17 phase I trials between January 2005 and June 2010 were analyzed at our institution. Results: The histological types were: adenocarcinoma (79%), squamous cell carcinoma (13%), and others. Patients received a median number of 3 prior lines of treatment befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Sites #2, #6, #7, #10, and #15 are relatively new phase I programs and have benefited from this class of clinical study. Retrospective analyses of patients treated on primarily phase IB studies for gastrointestinal cancer and lung cancer showed response rate (RR) of 4% and 16% and stable disease of 38% and 41%, respectively . Further, in genomically matched patients, phase I trials yielded a RR of 27% .…”
Section: Discussionmentioning
confidence: 99%
“…Sites #2, #6, #7, #10, and #15 are relatively new phase I programs and have benefited from this class of clinical study. Retrospective analyses of patients treated on primarily phase IB studies for gastrointestinal cancer and lung cancer showed response rate (RR) of 4% and 16% and stable disease of 38% and 41%, respectively . Further, in genomically matched patients, phase I trials yielded a RR of 27% .…”
Section: Discussionmentioning
confidence: 99%
“…None of the randomized prospective studies that evaluated a single-agent ICI used a placebo, which seems ethically appropriate, and used docetaxel instead. Moreover, significant clinical benefit for patients with NSCLC treated in phase 1 trials has been reported, and experimental agents in early phase studies might also have a detrimental effect, so we considered a chemotherapy cohort the most appropriate. The “disease-stabilizing effect” of late lines of chemotherapy treatment seems uncertain.…”
mentioning
confidence: 99%